Prikrite nevarnosti v simulacijskem centru - Križmarić, Miljenko (Zdravniški vestnik, 2011)
In the article, we emphasize the need for all equipment in a simulation centreto be maintained in excellent working condition, and present a case of nitrous oxide (N2O) leakage through a damaged pressure regulator. For a considerable time faulty operation of the pressure-reducing valve went unnoticed, resulting in slow, imperceptible leakage of gas from the cylinder. A careful soap test revealed that gas was escaping through a small nozzle on the back of the pressure regulator. The leakage was inaudible but could be felt by placing a finger on the valve nozzle. Great care must be exercised when using reduction valves, and pressure testing of the entire circuit is mandatory even if the system is small. We recommend a simple test for gas leakage, performed by placing a finger on possible openings in valves or connecting tubes, which is suitable for use both in a simulation centre and inreal circumstances.
Keywords: medicinska oprema; security; simulacijski modeli; varnost; zapleti